Formação de professores/as para o ensino das relações étnico-raciais em cursos de Pedagogia no Estado do Pará - AMARANTE, Karolina Carvalho do (Universidade Federal do Oeste do Pará, 2023)
The research investigates the training of teachers for ethnic-racial relations, in Pedagogy courses at four federal public universities located in the State of Pará (Universidade Federal do Pará - UFPA, Universidade Federal do Pará, Federal University of the West of Pará - UFOPA, Federal Rural University of the Amazon - UFRA and Federal University of the South and Southeast of Pará -UNIFESSPA) in the perspective of Law No. 11.645/08 and Resolution CNE/CP 01/2004. It seeks to reveal: To what extent has the inclusion of Teaching for Education of Ethnic-Racial Relations in the curriculum of Pedagogy courses at these universities contributed to qualify teachers for the promotion of an anti-racist education? For this, we used bibliographic and documental research, in the perspective of understanding educational policies for the ethnic-racial theme from the 90's onwards, its advances, limits and contradictions through a survey of academic productions on the researched object and documents produced by the researched institutions such as the Pedagogical Course Projects (PPC). In addition, we applied questionnaires to professors who teach subjects about ERER in their respective courses, with the objective of knowing the training of professors who teach ERER contents and what their conceptions and experiences about the inclusion of this policy in teacher education are /at. The results point to advances in terms of the presence of subjects related to ethnic-racial issues, but we identified that the course of formation of the courses seeks to satisfy legal demands in a peripheral and protocol way, without incorporating into the institutional demands of the perspective of an anti-racist education.